ETHNO-CULTURAL SPECIFICITY OF THE SUBJECTIVE COMPLEXITY OF THE LIE MANIFESTATION - Chakhoyan, A.S. (Modern Psychology, 2019)
The ethno-cultural factor influence on the person’s behavior involves many aspects, including the lie attitude, particularly the lightness of lie. Lying is a complex psychological act that requires cognitive effort and the overcoming of value and moral barriers. The results of this investigation indicate general tends of lie using complexity inherent in the certain ethnic groups’ representatives.
Keywords: lie, lie using complexity, attitude to lies, ethnic group.